2019
DOI: 10.1107/s2053230x1901464x
|View full text |Cite
|
Sign up to set email alerts
|

The non-swapped monomeric structure of the arginine-binding protein from Thermotoga maritima

Abstract: Domain swapping is a widespread oligomerization process that is observed in a large variety of protein families. In the large superfamily of substrate-binding proteins, non-monomeric members have rarely been reported. The arginine-binding protein from Thermotoga maritima (TmArgBP), a protein endowed with a number of unusual properties, presents a domain-swapped structure in its dimeric native state in which the two polypeptide chains mutually exchange their C-terminal helices. It has previously been shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The structure of cs-TmArgBP ΔCTH refers to the structure of closed-state conformation of TmArgBP without the CTH (PDB: 6GGV). Recently, the crystal structure of a monomeric version of the protein in the closed-state conformation complexed with arginine has also been solved (PDB: 6SVF, which is referred as cs-TmArgBP CTH ) ( Smaldone et al, 2019 ). In this structure a proline residue occurring prior to CTH is mutated (P215GK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of cs-TmArgBP ΔCTH refers to the structure of closed-state conformation of TmArgBP without the CTH (PDB: 6GGV). Recently, the crystal structure of a monomeric version of the protein in the closed-state conformation complexed with arginine has also been solved (PDB: 6SVF, which is referred as cs-TmArgBP CTH ) ( Smaldone et al, 2019 ). In this structure a proline residue occurring prior to CTH is mutated (P215GK).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a monomeric version of the arginine-bound closed-state conformation of TmArgBP has been solved. In this structure more flexibility is introduced in the loop prior to CTH by mutating PRO-215 with GLY(2 1 5)-LYS(2 1 6) enabling the CTH to fold against the same chain ( Smaldone et al, 2019 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein presents a number of distinctive/unique features in the large class of SBP. Although substrate-binding proteins are generally monomeric, TmArgBP is essentially dimeric, with the concomitant presence, as minor components, of higher oligomerization states [ 14 , 15 , 16 ]. The crystallographic structure of the protein has highlighted that its dimer is stabilized by swapping of the terminal C -terminal helix [ 9 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have exploited the extraordinary stability of TmArgBP to effectively manipulate the protein through mutation, truncation and dissection of its native structure [ 10 , 13 , 14 ]. In particular, we have shown that a stable monomeric form may be obtained either though site-directed mutagenesis [ 15 ] or through the deletion of the C -terminal end, the swapping element in the protein binding [ 10 ]. TmArgBP can be further manipulated by dissecting it into its constitutive D1 and D2 domains ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%